Penguatan Pendidikan Karakter Berbasis 8 Dimensi Profil Lulusan Pancasila Dalam Upaya Pencegahan Bullying di MI Muhammadiyah Maliba - Shafna Adzani; M.Yunus Sudirman; Ahmad Kamil (STKIP Subang, 2026)
This study aims to describe the strengthening of character education based on the eight dimensions of the Pancasila Graduate Profile in preventing bullying at MI Muhammadiyah Maliba. This research uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students. The results showed that character education strengthening was implemented through learning activities, habituation, and school programs. The developed character values include faith, cooperation, independence, responsibility, critical thinking, creativity, communication, and social awareness. The bullying behavior found was mainly verbal bullying, such as teasing among students. Bullying prevention efforts were carried out through teacher guidance, character building, mutual respect habituation, and direct handling of bullying behavior. Supporting factors include school commitment, positive school culture, habituation programs, and parental support, while inhibiting factors include external influences, social media, and students’ lack of awareness. Therefore, strengthening character education based on the eight dimensions of the Pancasila Graduate Profile contributes to creating a safe and conducive school environment.